Coupling of a voltage‐gated Ca2+ channel homologue with a plasma membrane H+‐ATPase in yeast. (9th December 2016) - Cho, Toshihiko; Ishii‐Kato, Aya; Fukata, Yuko; Nakayama, Yoshitaka; Iida, Kazuko; Fukata, Masaki; Iida, Hidetoshi
Abstract : Yeast has a homologue of mammalian voltage‐gated Ca 2+ channels (VGCCs), enabling the efficient uptake of Ca 2+ . It comprises two indispensable subunits, Cch1 and Mid1, equivalent to the mammalian pore‐forming α1 and auxiliary α2 /δ subunits, respectively. Unlike the physiological roles of Cch1/Mid1 channels, the regulatory mechanisms of the yeast VGCC homologue remain unclear. Therefore, we screened candidate proteins that interact with Mid1 by an unbiased proteomic approach and identified a plasma membrane H + ‐ATPase, Pma1, as a candidate. Mid1 coimmunoprecipitated with Pma1, and Mid1‐EGFP colocalized with Pma1‐mCherry at the plasma membrane. The physiological relevance of their interaction was determined using the temperature‐sensitive mutant, pma1‐10 . At the nonpermissive temperature, the membrane potential was less negative and Ca 2+ uptake was lower in pma1‐10 than in wild‐type cells. Increased extracellular H + increased the rate of Ca 2+ uptake. Therefore, H + extrusion by Pma1 may be important for Ca 2+ influx through Cch1/Mid1. These results suggest that Pma1 interacts physically with Cch1/Mid1 Ca 2+ channels to enhance their activity via its H + ‐pumping activity. Abstract : Cch1/Mid1 calcium channel is a yeast homologue of mammalian voltage‐gated calcium channels. In this report, we suggest that Mid1 physically interacts with Pma1, a plasma membrane H + ‐ATPase and that the H + ‐pumping activity of Pma1 is important for the activation of the Cch1/Mid1 calcium channel.